Ontology matching: in search of challenges ahead - Farooqui, N.K.; Noordin, Mohamad Fauzan; Muhammad, AbdulHafeez (JATIT.org, 2015)
This paper presents key features and challenges for the development of the next generation ontology matcher. Matching elements of two data instances plays an important role in e-business, multilingual data instances, biomedical and open data cloud. This paper elaborates technologies, tools, algorithms and methods used by recent ontology matchers. Ontology matching has become a Meta Research field where research topics such as developing advanced reasoner, algorithms for optimum matching, working on Meta matchers and improving results are major open research areas. In order to find the future direction towards the development of optimum matchers we illustrated a list of future challenges, key features, and their importance. This paper does not propose solution or framework for an optimum matcher. Reader will get help in deciding next ontology matching techniques in his domain of ontology matching research.